2012
DOI: 10.1186/2040-2392-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of novel fine-scale structural variation at autism spectrum disorder candidate loci

Abstract: BackgroundAutism spectrum disorders (ASD) represent a group of neurodevelopmental disorders characterized by a core set of social-communicative and behavioral impairments. Gamma-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the brain, acting primarily via the GABA receptors (GABR). Multiple lines of evidence, including altered GABA and GABA receptor expression in autistic patients, indicate that the GABAergic system may be involved in the etiology of autism.MethodsAs copy number variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
1
24
2
Order By: Relevance
“…Contrary to our findings, a recent search for CNVs in GABA pathway genes [44] did not find an enrichment of duplications in this region. Rather, both deletions and duplications were observed at similar frequencies in cases and controls.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, a recent search for CNVs in GABA pathway genes [44] did not find an enrichment of duplications in this region. Rather, both deletions and duplications were observed at similar frequencies in cases and controls.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our findings, this study found GABR gene cluster duplications at similar frequencies in both cases and in controls (Table S2 in ref. [44]). In addition, deletions were more common in this study in both cases and controls, while duplications were more common in our data.…”
Section: Discussionmentioning
confidence: 99%
“…These deletions involve different molecular regions: the a isoform is affected in cases 1 and 3, whereas a and b isoforms are affected in case 2. Defects involving NRXN1-b appear to be rare compared to those involving only NRXN1-a (Duong et al 2012;Dabell et al 2013)Approximately 101 cases of CNVs in 2p16.3 including the NRXN1 gene have been described, 95 deletions and 6 duplications, with a mean size of 388.97 kb (Friedman et al 2006;Szatmari et al 2007;Kirov et al 2008;Zahir et al 2008;Rujescu et al 2009;Ching et al 2010;Magri et al 2010;Wisniowiecka-Kowalnik et al 2010;Duong et al 2012;Hedges et al 2012;Schaaf et al 2012;Bena et al 2013). The a isoform is affected in all cases, whereas the b isoform is additionally affected in only 21 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Structural variations (SVs), including deletions, duplications, insertions, inversions and translocations of at least 50bp, account for the largest number of divergent base pairs (bp) across human genomes 1 . SVs have been shown to contribute to polymorphic variation, pathogenic conditions, and large-scale chromosome evolution 2 , and several human diseases such as cancer 3 , autism 4 , or Alzheimer's 5 have been associated with SVs. SVs have also been shown to impact phenotypes for an increasing number of other organisms [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%